Examining economic incentives and youth engagement in cultural heritage conservation for tourism and sustainable development: A case study of cultural provinces in Vietnam - Nam, Nguyen Thanh; Thanh, Nguyen Nghi (Asian Development Policy Review, 2024)
This study examines the relationship between economic incentives and young people’s involvement in conserving cultural heritage within Vietnam’s cultural provinces. Using multivariable linear regression analysis on data from 200 randomly chosen participants, the main goal is to find out how different types of economic incentives can get more young people involved in preserving cultural heritage, which will help reach goals for sustainable development. The findings indicate a significant positive impact of job creation initiatives on youth engagement, underscoring the pivotal role of employment opportunities in aligning conservation efforts with sustainable development goals. Additionally, entrepreneurial support emerges as a critical factor, suggesting the necessity of nuanced strategies to optimize its efficacy. Furthermore, we identify skill development and educational support as vital for sustaining youth involvement in cultural heritage conservation, noting positive associations with grant opportunities, recognition, and awards. These results underscore the intricate interplay of various incentives in nurturing youth engagement. The study’s implications are far-reaching for policymakers, accentuating the importance of a comprehensive approach integrating economic incentives with educational support to foster youth participation in cultural heritage conservation. By providing insights into effective incentivization mechanisms, this research facilitates the formulation of targeted interventions and policy measures tailored to the distinctive context of Vietnam’s cultural provinces. Despite inherent limitations, this study significantly enhances our understanding of mobilizing youth for cultural heritage conservation in a manner that advances sustainable development objectives.